Tribological researches of electroerosive processing of steel details of cars - Marchenko, D.D.; Matvyeyeva, K.S. (Problems of Tribology, 2021)
The article considers the technology of electroerosive treatment of steel friction pairs and presents the results of experimental studies. Analysis of experimental studies has shown that an increase in the anode-cathode voltage leads to a sharp decrease in the microhardness of the surface layer. The study also allowed to determine the characteristic size of the structural elements, the height parameters of the surface roughness. The elemental composition of the initial surface of the sample made of steel 15HGN2TA differs from the composition of the coatings and surface layers of the samples modified by electroerosive treatment with different electrodes. In the mode of operation of the "anode - cathode" system on the cathode surface due to dissipative processes, a thin layer of coating of a stable modified structure is formed. It is shown that the height of surface irregularities in the areas after friction is higher than in the areas of the surface outside the friction track, which is associated with the formation on the surface of the samples of the friction transfer film. It was found that the frictional interaction of steel samples treated by electroerosion method forms a thin film on the friction surface of steel samples, which leads to a change in the topography of surfaces with increasing height of microroughnesses and structuring of the transfer film in the sliding direction. The influence of electroerosive treatment of steel surfaces on the wear resistance of the metal-polymer tribosystem was established and the optimal treatment modes were obtained: voltage U = 145-150 V, capacitor capacity C = 225-230 μF, treatment duration t = 3-4 min / cm2, providing the greatest reduction in speed wear of the polymer counterbody and recommended in the development of technological processes of electroerosive treatment.